UJI PERLAKUAN BENIH TERHADAP TINGKAT SERANGAN PENYAKIT BULAI (Peronosclerospora sp) PADA GALUR JAGUNG TETUA JANTAN SYNGENTA01 - Risky Nurfitriani Susanti; Suharjono Suharjono; Agus Supriono (Universitas Tribhuwana Tunggadewi, 2022)
Downey mildew is one of the most significant corn diseases that has caused huge losses to farmers and threatened food security. This study aimed to know the effect of Oksatiupiprolin and Thiamethoksam, also the treatment of Fenamidon on Downey mildew attack level. This study used Randomized Complete Blok Design non-factorial consisting of no treatment (P1), Thiamethoksam, 2.5 ml/kg + Fenamidon 6 ml/kg + Mefenoksam 3 ml/kg (P2) and Thiamethoksam 2.5 ml/kg + Okasatiupiprolin 4 ml/kg (P3) each of treatments replicated three times. The result was showed no treatment(P1)and Thiamethoksam2.5 ml/kg + Fenamidon 6 ml/kg + Mefenoksam 3 ml/kg(P2) was not significant to all tested parameters. The Thiamethoksam 2.5 ml/kg + Okasatiupiprolin 4 ml/kg (P3) treatment showed was not significant to the parameter of the number of the plants attacked by disease and healthy plants, attack time, and attack fluctuation, yet the (P3) treatment showed significant to the attack number of disease is 110,2 plants and percentage parameter of Downey mildew is 9,58%.